Cointegrated vector autoregressive processes with continuous structural changes - Antti Ripatti; Pentti Saikkonen (Bank of Finland, 1998)
We extend the conventional cointegrated VAR model to allow for general nonlinear deterministic trends.These nonlinear trends can be used to model gradual structural changes in the intercept term of the cointegrating relations.A general asymptotic theory of estimation and statistical inference is reviewed and a diagnostic test for testing the correct specification of an employed nonlinear trend is developed.The methods are applied to Finnish interest rate data.A smooth level shift of the logistic form between the own-yield of broad money and the short-term money market rate is found appropriate for these data.The level shift is motivated by the deregulation of issuing certificates of deposit and its inclusion in the model solves the puzzle of 'missing cointegration vector' found in a previous study.
URN:NBN:fi:bof-20140807181
Keywords: 330; cointegrated VAR model; gradual structural change; nonlinear deterministic trend